Milk yield of Simmental × Zebu and Brown Swiss × Zebu cows in tropical climate. - Ríos-Utrera, Ángel (2015)
The objective of the present study was to determine the milk yield of Simmental-Zebu and Brown Swiss-Zebu cows with different proportions of Bos taurus genes. The study was carried out from 1985 to 2007 at the the Instituto Nacional de Investigaciones Forestales, Agrícolas y Pecuarias, Playa Vicente research station (Veracruz, Mexico). The site presents a humid tropical climate. Milk yield records of Simmental × Zebu and Brown Swiss × Zebu cows with different proportions of Bos taurus genes (50, 62.5 or 75%) were analyzed. The cows were maintained in rotational grazing of the introduced pastures: Star grass (Cynodon plectostachyus) and Guinea (Panicum maximum), and were milked twice a day, after a restricted suckling by their calves. Calves were weaned at 210 days of age. The statistical model included the fixed effects of breed group, year of calving, season of calving, lactation number, and lactation length as a linear covariate; in addition, the model included sire of the cow within breed group as a random effect. The lactation length of Brown Swiss × Zebu cows was greater (P<0.05) than that of Simmental × Zebu cows. Milk yield per lactation, per day and per calving interval of Simmental × Zebu and Brown Swiss × Zebu cows were similar. Third-parity cows yielded more milk (P<0.001) per lactation, per day and per calving interval than first- and second-parity cows. Second-parity cows yielded more milk (P<0.001) per lactation, per day and per calving interval than first-parity cows.